Staggered public procurement of food grains in Punjab: New policy regime - SINGH, SUKHPAL; SEKHON, M K; KUMAR, SUNNY (The Indian Journal of Agricultural Sciences, 2021)
Punjab has been significantly contributing to the central pool of food reserves. But the marketing efficiency of farm produce must be improved in the context of new policy regime. The present study was undertaken during 2019–20 to examine the farmers’ perspectives and challenges that emerged in the initiation of an alternative procurement approach for foodgrains. The results revealed that the marketed surplus of wheat was around 232 q and about 90% of the wheat production is being sold in the market. The selected farmers sold about 95% of their marketed surplus in the postharvest period and just 5% sold during the lean period in case of wheat crop. Further, among all the categories, the large farmers sold their produce in a lean period followed by medium and small farmers. The month-wise pattern of the total market arrival clearly revealed that more than 90% of the wheat arrived during the month of April and May and prices of wheat crops fluctuate during the lean period. On the other hand, the largest volume of paddy arrived in the month of October and November and paddy price remained almost at par with MSP in the post-harvest period. By considering all the aspects, it was found that the scheme of staggered procurement is feasible for the wheat crop only as the majority of farmers were willing to adopt this scheme. In the whole process, the additional income to the farmers comprises a sum of ₹ 900 crores in the marketing season of the wheat crop.